Synthesis, characterizations, and electrochemical studies of ZnO/reduced graphene oxide nanohybrids for supercapacitor application. (June 2021) - Rai, S.; Bhujel, R.; Khadka, M.; Chetry, R.L.; Swain, B.P.; Biswas, J.
Abstract: Herein the present article reports the fabrication of ZnO/reduced graphene oxide (ZnG) nanohybrid following a reduction-based process using a non-hazardous material, i.e., ascorbic acid. The morphology, structure, and bonding in the nanohybrid were analyzed using different techniques. Atomic force microscopy and scanning electron microscopy images show spherical particles of ZnO distributed over reduced graphene oxide (rGO). The X-ray diffraction analysis gives calculated values of crystallite size for ZnO as 15.62 nm. The successful incorporation of ZnO nanoparticles into rGO was confirmed using energy-dispersive X-ray spectroscopy and X-ray photoelectron spectroscopy analyses. The electrochemical studies were performed using an electrolyte (0.5 M H2 SO4 ). The calculated value of specific capacitance for the nanohybrid was 345 Fg -1, which was found to be almost double as compared to that of rGO, which is having a value of only 190.5 Fg -1 at the same scan rate. The nanohybrid also showed excellent capacitance retention after 1, 000 cycles. Graphical abstract: Image 1 Highlights: ZnG nanohybrid was synthesized using a simple and cost-effective method. The incorporation of ZnO nanoparticles in rGO lead to the formation of ZnG nanohybrid was revealed. ZnG nanohybrid showed excellent capacitance retention.